A Graphene–Pure‐Sulfur Sandwich Structure for Ultrafast, Long‐Life Lithium–Sulfur Batteries. (4th November 2013) - Zhou, Guangmin; Pei, Songfeng; Li, Lu; Wang, Da‐Wei; Wang, Shaogang; Huang, Kun; Yin, Li‐Chang; Li, Feng; Cheng, Hui‐Ming
<x xml:space="preserve">Abstract</x> A unique sandwich structure is designed with pure sulfur between two graphene membranes, which are continuously produced over a large area, as a very simple but effective approach for the fabrication of Li–S batteries with ultrafast charge/discharge rates and long lifetimes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>